Microstructural effect of a laser-activated bleaching agent containing titanium dioxide on human enamel - Besegato, Joao Felipe [UNESP]; Silva, Aryvelto Miranda [UNESP]; De Almeida, Eran Nair Mesquita [UNESP]; De Souza Rastelli, Alessandra Nara [UNESP]; Takahashi, Ricardo; Dezan-Garbelini, Cassia Cilene; Hoeppner, Márcio Grama (My University, 2020)
Aim: This study aimed to evaluate the effect of a laser-activated bleaching agent containing titanium dioxide (TiO2) nanoparticles on enamel roughness and hardness. Materials and Methods: Twenty human premolars were randomized into two groups according to the bleaching treatments performed: HP-35% hydrogen peroxide and HP + TiO2-30% hydrogen peroxide containing TiO2 light-activated by diode laser (980 nm). It was performed two bleaching sessions with an interval of 7 days. Microhardness and roughness of the enamel were assessed at three times: T0-Before 1st appointment, T1-after 2nd appointment, and T2-7 days after 2nd appointment. Results: The HP + TiO2 did not cause changes on enamel roughness and hardness and presented the same effects of the HP. Conclusions: Both bleaching agents showed no difference between them. Then, it is possible to conclude that both are viable for clinical use during in-office dental bleaching technique regarding the microstructural changes that they might cause.
Keywords: Hardness; hydrogen peroxide; laser; roughness; titanium dioxide